Pengaruh Variasi Dosis Iradiasi Gamma pada Pemisahan Komponen Penyusun Biomassa Lignoselulosa Sabut Kelapa - Harum Azizah Darojati; Sebastianus Dani Ganesha; Dhita Ariyanti (Center for Pulp and Paper, 2022)
The Effect of Gamma Iradiation Dosage Variation on The Separation of Coconut Coir Lignocellulose Biomass ComponentsAbstractIndonesia has the potential for lignocellulosic biomass in the form of coconut coir, which is very abundant. The components of coconut coir are lignocellulosic biomass, which consists of cellulose, hemicellulose, and lignin and can be separated from one another. This study was conducted to determine the effect of variations in the dose of gamma-ray irradiation on the structure of each component so that it was expected that the utilization of coconut coir lignocellulosic biomass could be more comprehensive. The separation was carried out using wet irradiation with a 5% H2O2 solution as the initiator, where 15 grams of coco coir sample was dissolved in 60 ml of 5% H2O2 solution. Gamma irradiation dose variations were 0 kGy, 50 kGy, 100 kGy, 150 kGy, and 200 kGy. Based on the research, the optimal dose to obtain glucose was obtained at an irradiated dose of 100 kGy with a glucose level of 5.09 mg. The optimal gamma irradiation dose for lignin separation is 50 kGy with a lignin separation percentage of 34.95%. Based on the FTIR analysis, it can be seen that as a result of the chemical bond resulting from the separation, there is a decrease in the effect of the gamma IR radiation. This study showed that the separation of lignocellulosic coconut coir biomass using gamma irradiation could produce higher levels of glucose and lignin separation and affect the chemical structure of cellulosic biomass